2016
DOI: 10.1111/gcb.13403
|View full text |Cite
|
Sign up to set email alerts
|

Rapid carbon loss and slow recovery following permafrost thaw in boreal peatlands

Abstract: Permafrost peatlands store one-third of the total carbon (C) in the atmosphere and are increasingly vulnerable to thaw as high-latitude temperatures warm. Large uncertainties remain about C dynamics following permafrost thaw in boreal peatlands. We used a chronosequence approach to measure C stocks in forested permafrost plateaus (forest) and thawed permafrost bogs, ranging in thaw age from young (<10 years) to old (>100 years) from two interior Alaska chronosequences. Permafrost originally aggraded simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
130
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(146 citation statements)
references
References 89 publications
8
130
8
Order By: Relevance
“…Moreover, a long‐term hiatus in the accumulation record may occur, as has been detected in the age‐depth model of Sei2 (see also Routh et al, ; Sannel et al, ). In addition, the very low CARs, when followed by thaw, could also be the results of peat decomposition of the formerly frozen peat layers upon thaw (see Jones et al, ; O'Donnell et al, ). In contrast, permafrost thaw may have resulted in also very high ACARs (>50 g C m −2 year −1 ) as recorded in Ind4 and Ind5, where Sphagnum is encouraged to grow in situ by the hydrological changes brought about by warming (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a long‐term hiatus in the accumulation record may occur, as has been detected in the age‐depth model of Sei2 (see also Routh et al, ; Sannel et al, ). In addition, the very low CARs, when followed by thaw, could also be the results of peat decomposition of the formerly frozen peat layers upon thaw (see Jones et al, ; O'Donnell et al, ). In contrast, permafrost thaw may have resulted in also very high ACARs (>50 g C m −2 year −1 ) as recorded in Ind4 and Ind5, where Sphagnum is encouraged to grow in situ by the hydrological changes brought about by warming (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Intense permafrost thawing eventually causes peatland collapse and saturation with thaw water potentially leading to increase in carbon sequestration through increased NPP and decreased CO 2 emissions, although wetting promotes CH 4 emissions (Swindles et al, ). Also some studies suggest that critical loss of sporadic and discontinuous permafrost in the coming century may lead to a loss of the large deep C storage (Jones et al, ; Schuur et al, ). Thereby in the future the net effect can either be an increase or a reduction in ACARs, or even turning the site to a net C source (Chaudhary et al, ; Wang et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inundation results in anaerobic conditions associated with elevated emissions of CH 4 (Wickland et al, ) but can also restrict respiration of old C that previously was respired aerobically in the active layer (Schädel et al, ) further enhancing C accumulation. Despite high accumulation rates of surface peat following thaw, studies along Alaskan thaw chronosequences indicated large net losses of C in the initial decades to centuries following thaw, in the order of <500 to 3,500 g C m −2 yr −1 during the first decade following thaw (Jones et al, ; O'Donnell et al, ). However, various field studies from areas with different permafrost and developmental histories have found no direct evidence of losses of old soil C as CO 2 or CH 4 following thaw at the magnitude that would be necessary for such large net C losses (Cooper et al, ; Estop‐Aragonés, Cooper, et al, ; Estop‐Aragonés, Czimczik, et al, ; Klapstein et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, poorly drained peatland permafrost sites typically thaw and then flood, forming collapse scar wetlands that are dominated by anaerobic conditions [ Bellisario et al , ]. Poorly drained syngenetic permafrost sites may also experience high C loss rates [e.g., O'Donnell et al , ] or decreased C accumulation following thaw [ Jones et al , , ] as large stores of previously (and rapidly) frozen (i.e., microbially unavailable) labile C become accessible [ Schädel et al , ]. However, at our site, the bulk of the peat was apparently established under wetland conditions prior to the initiation of permafrost [ Zoltai , ].…”
Section: Introductionmentioning
confidence: 99%